The strategy for planning the future of a Christian believer in the exegetical context of James 4:13–15 - Pružinský, Štefan (HTS teologiese studies, 2021)
This article deals primarily with the examination of two key and exegetically demanding expressions in the text of the General Epistle of James, which relate to fundamental biblical principles on planning the future of the believer and reconciling human life with God’s will expressed in Holy Scripture. The first one is the hapax legomenon Ἄγε νῦν, the significance of which is closely related to updating of the affected principles with practice. The second term is ποιήσοµεν, which, in most translations, translates as ‘remain’ and does not reflect the core idea of the examined verse. We prove that a more authentic and appropriate translation is ‘work’. Our aim was to find out what new interpretive possibilities the original biblical text offers. The constitutive starting point for research is Novum Testamentum Graecum – Editio Critica Maior. We then compared these texts with the Slovak Ecumenical Bible. The method of our exegetical work was not primarily comparison, but a linguistic analysis and historical-critical exegesis, the result of which is a completely new proposal for the translation of the scrutinised texts. Auxiliary materials were the most important patristic and exegetical commentaries. In conclusion, we state that the analysis made it possible to find a new translation of the researched text, which can really contribute to the improvement of further review and publication of the ecumenical translation of the Bible into various languages.Contribution: The article examines the source Greek biblical text of James 4:13–15 and reveals a new interpretation of it. This interpretation brings a new, biblical light into the field of planning, which is one of the most current topics nowadays. With its content and especially its conclusions, it contributes to the goals of this theological journal, the subject of which is also the research of Greek biblical manuscripts.